Estudo dos polimorfismos DUFFY em pacientes infectados com Plasmodium vivax - Ali, Rechfy Kasem Abou (2015)
Introduction: Malaria is a major public health problem, including Brazil, where the Plasmodium vivax is more prevalent. The Duffy glycoprotein acts as facilitator in the tissue invasion of erythroid by P. vivax; however, little is known about the association between DUFFY polymorphisms and malaria susceptibility caused by this type of plasmodium. New perspectives about this subject have emerged in different endemic regions also involving the parasite density infections. Objective: To investigate the impact of DUFFY polymorphisms in patients infected by Plasmodium vivax Materials and Methods: It was studied DNA samples of Patients infected by P. vivax, diagnosed in the Formation of Tropical Medicine Doctor Heitor Vieira Dourado through laboratorial tests which defined the type of malaria parasitaemia as the thick smear methods, genotyping and WBC. The verification of Duffy polymorphisms were carried out in the Amazon Blood Center, through PCR / RFLP and microarray method (Beadchip). The statistical significance of the frequencies found were analyzed using the statistical package R Core Team 2013. Results: We studied 287 patients and 273 individuals with no history of malaria. The FYBES allele was found in 53.2% of subjects with no history of malaria and 11.2% of infected patients. The FYB allele seems to be associated with middle and high parasite density. Discussion: Duffy polymorphism has been considered to be important in areas where P. vivax predominates. In the present study we confirm the FYBES allele is directly associated with a reduced expression of the glycoprotein Duffy, which may have an impact on malarial infection. Conclusion: Duffy polymorphisms may be associated as the frequency of parasite infection well as the density and the severity of the clinical manifestations.